PELAKSANAAN PROGRAM KAMPUS MENGAJAR ANGKATAN IV DI SD NEGERI 205 PADANG LOANG KABUPATEN BONE - Adhan Fauzi Al Hakim; Nursalim (Jurnal Abdi Masyarakat Pendidikan, 2024)
The Teaching Campus is part of the learning and teaching activities in the basic education unit of the Merdeka Belajar Kampus Merdeka (MBKM) program which aims to provide opportunities for students to learn and develop themselves through activities outside the classroom. The Teaching Campus Program at UPT SDN 205 Padang Loang consists of several activities, namely debriefing, fielding, observation and program planning. In general, the Teaching Campus activities at UPT SDN 205 Padang Loang were carried out well and smoothly, as can be seen from the activities that have been carried out such as helping with teaching activities (literacy and numeracy), helping with technology adaptation (providing technology classes and optimizing learning media), helping with administration (healthy Friday movement activities, making class posters, and improving classes), as well as other collaborative action programs (religious activities, English classes, achievement stars, flag ceremony training, scouting, Sports and Arts Week, and independence competition activities)